2004
DOI: 10.1037/0278-7393.30.6.1252
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Ambiguity and the Process of Generating Meaning From Print.

Abstract: An ambiguity disadvantage (slower responses for ambiguous words, e.g., bank, than for unambiguous words) has been reported in semantic tasks (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
110
7
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(134 citation statements)
references
References 54 publications
16
110
7
1
Order By: Relevance
“…The absence of a number-of-senses effect on semantic classification RTs is interesting and is consistent with recent demonstrations that although ambiguity effects may not be reflected in semantic classification RTs (Pexman, Hino, & Lupker, 2004), they can be detected using neuroimaging techniques (Hargreaves et al, 2011). Of course, despite its greater objectivity, number of senses is, at best, a crude proxy for ambiguity, since it does not distinguish between related and unrelated multiple definitions.…”
Section: Discussionsupporting
confidence: 71%
“…The absence of a number-of-senses effect on semantic classification RTs is interesting and is consistent with recent demonstrations that although ambiguity effects may not be reflected in semantic classification RTs (Pexman, Hino, & Lupker, 2004), they can be detected using neuroimaging techniques (Hargreaves et al, 2011). Of course, despite its greater objectivity, number of senses is, at best, a crude proxy for ambiguity, since it does not distinguish between related and unrelated multiple definitions.…”
Section: Discussionsupporting
confidence: 71%
“…That is, words with more definitions produce a response advantage in lexical decision (''does the letter string spell a word? ''), whereas the same words show a diminished effect when the semantic requirements of the task are reduced by either changing the foils to be illegal nonwords (i.e., letter strings without vowels) or changing the task to simple naming (Borowsky and Masson 1996; see also Pexman et al 2002Pexman et al , 2004. Pexman et al (2002) have also suggested that semantic richness (i.e., number of semantic features that an object has) facilitates word recognition, and their results indicate that the number of semantic features accounts for close to 50% of the variance in lexical decision reaction time, and about half of that in naming reaction time.…”
Section: Cortical Activation During Semantic Processing Of Actionmentioning
confidence: 97%
“…Likewise, while words with more senses (i.e., more ambiguous) enjoy a processing advantage in lexical decision, the effect of ambiguity is less clear in tasks which place an emphasis on semantic activation, such as semantic categorization or semantic relatedness (i.e., are these two words related?). Specifically, there is in some cases an ambiguity disadvantage in semantic relatedness (Hoffman & Woollams, 2015;Pexman, Hino, & Lupker, 2004;Piercey & Joordens, 2000) while ambiguity effects are either inhibitory or null in semantic categorization . By ascertaining how stimulus quality and semantic variables modulate the shape, rather than just the mean, of distributions, one may find dissociations that are apparent only at the level of distributional characteristics.…”
Section: The Present Studymentioning
confidence: 99%